2022
DOI: 10.1055/a-1924-8008
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Tungstate Dihydrate (Na2WO4·2H2O): A Mild Oxidizing and Efficient Reagent in Organic Synthesis

Abstract: The reagent sodium tungstate dihydrate has some special features which are very important in synthesis. For instance, it is a mild and efficient reagent used in oxidation. Based on reports from recent literature we are proposing this spotlight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…49 Sodium tungstate is employed as a catalyst in organic chemistry for the epoxidation of alkenes and the oxidation of alcohols to aldehydes or ketones indicating its greater tendency to act as an oxidizing agent. 50 In the presence of light, sodium silicate functions as a mild reducing agent. As a result, no tubes are formed in the case of silver silicate that was kept under light due to the quick reduction of silver ions to metallic silver under light.…”
Section: Discussionmentioning
confidence: 99%
“…49 Sodium tungstate is employed as a catalyst in organic chemistry for the epoxidation of alkenes and the oxidation of alcohols to aldehydes or ketones indicating its greater tendency to act as an oxidizing agent. 50 In the presence of light, sodium silicate functions as a mild reducing agent. As a result, no tubes are formed in the case of silver silicate that was kept under light due to the quick reduction of silver ions to metallic silver under light.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have also reported encouraging results concerning the use of tungstate-based ILs for the catalysis reaction of CO 2 with substrates like diamines, propargylic amines, aminophenols, aminothiobenzenes, and cyanoanilines for the preparation of corresponding cyclocarbonated compounds [53][54][55][56][57] or for the conversion of cyclic carbonates into linear ones [58]. In addition to this, tungstate salts have shown interesting catalytic performances in the catalysis of oxidative reactions like the preparations of carboxylic acids and aldehydes as well as sulfones and epoxides [59,60]. Concerning epoxidations, apart from classic tungstate salts, the use of tungstate ILs has also been investigated, producing positive outcomes [53,56].…”
Section: Introductionmentioning
confidence: 96%